Acute liver failure as a presenting feature in an adolescent with acute lymphoblastic leukemia: A case report with review of literature - Simran Bhatnagar; Bharat Kumar; Nitish Kumar; Alok Hemal (Indian Pediatrics Case Reports, 2023)
Background: Acute lymphoblastic leukemia (ALL) is a common pediatric malignancy, typically manifesting with symptoms of bone marrow and hematolymphoid organ infiltration. Although hepatic involvement in the form of hepatosplenomegaly is seen in nearly two-thirds of the patients, primary presentation as acute liver failure is rare. Clinical Description: A 12-year-old boy presented with complaints of abdominal distention with jaundice for the past 15–20 days, associated with transient fever of 6 days. Examination revealed pallor, icterus, and hepatosplenomegaly. A possibility of acute infectious or autoimmune hepatitis or hemolytic anemia was considered. Management: Liver function tests were deranged with hyperbilirubinemia with modest increase in transaminases and serum alkaline phosphatase along with deranged prothrombin time. The complete blood count showed pancytopenia with normal peripheral smear. Investigations for common infectious causes were noncontributory, as also those for autoimmune hepatitis. The direct Coombs test was also negative. In view of persistent pancytopenia with hyperbilirubinemia and hepatosplenomegaly, a bone marrow evaluation was done, which revealed B-cell ALL (B-ALL). Thus, the child was diagnosed with a case of ALL presenting with acute liver failure. The child was initially managed as a case of acute liver failure and on diagnostic confirmation, he was started on the B-ALL chemotherapy protocol as per his risk stratification with hepatic dose modification of chemotherapy. The child showed complete normalization of the liver functions by about 4 weeks of induction chemotherapy and achieved remission. Conclusions: A child presenting with acute liver failure may be having an underlying undiagnosed, clinically silent ALL. After ruling out common causes of acute liver failure, one must not forget the possibility of leukemic blast infiltration of the liver as a cause of liver failure. With early initiation of advanced chemotherapeutic induction regimens, there can be dramatic resolution of liver injury and remission of ALL.